Joint statistical papers of Akahira and Takeuchi - Akahira, Masafumi, 1945- (World Scientific, 2003)
Masafumi Akahira and Kei Takeuchi have collaborated in research on mathematical statistics for nearly thirty years and have published many articles and papers. This volume is a collection of their papers, some published in well-known and others in lesser-known journals. The papers cover various fields, but the main subject is the theory of estimation -- asymptotic, non-regular, sequential, etc. All the papers are theoretical in nature, but have implications for applied problems.